Glencoe literature: the reader's choice American literature - Beverly Ann Chin et. al. (Unites States of America : Glencoe McGraw-Hill, 2000)
Each spring, rains come to the land now called texas. Covering the rolling hills and dessert country side, beautiful wildflowers- as blue jay feather and shaped like bonnets- blossom in the rain.
Unit1. From the earliest days -- Unit2. A new nation -- Unit3. The civil war and its aftermath -- Unit4. Regionalism and realism -- Unit5. Beginnings of the modern age -- Unit6. Midcentury Voices -- Unit7. Toward the Twenty-first century .
Keywords: TEXAS STORY